Artificial Authors: A Case For Copyright In Computer-Generated Works - Brown, Nina I. (Science and Technology Law Review, 2019)
For years, computers have dominated humans at chess, poker, and even Jeopardy!. Now, they are competing in the arts. Increasingly sophisticated artificial intelligence is creating music, art, and stories. Though the purpose of copyright law is to encourage this exact type of artistic production, none of these works are protected, because the United States Copyright Office has determined that only humans can author copyrightable works. This requirement—not mandated by the Constitution or Congress—was developed in an era where computer-generated creativity worth protecting was simply unimaginable. But years have passed, technology has advanced, and machines are now capable of developing dynamic and even award-winning creative works. Instead of accepting that the law must lag behind technology, this Article explores whether copyright law can—and should—evolve.